The Flying Beaver Brothers and the evil penguin plan - Eaton, Maxwell, III (Eaton, Maxwell, III. Flying beaver brothers, 2012)
Meet Ace and Bub, the flying beaver brothers! Ace loves extreme sports and is always looking for a new adventure. Bub loves napping and, well, napping. But when penguins threaten to freeze Beaver Island for "resort and polar-style living," the brothers put their talents to work saving their tropical island paradise. Can they save Beaver Island from environmental destruction? And can they do it in time to still win the annual Beaver Island Surfing Competition?